Factors Associated with Dental Care Utilization among Pregnant Women at Klapanunggal Health Centre, Bogor, Indonesia - Itsna Widita; Sutanto Priyo Hastono (Journal of Health Promotion and Behavior, 2019)
Background: Oral health care during pregnancy is important for the health of the mother and child.During pregnancy, many changes occur in oral cavity that can be linked to periodontal disease, including gingivitis and periodontitis. Oral health condition of pregnant women may adversely bring impacts such as preterm low birth weight (PLBW) and premature birth. Pregnant women need to regularly check oral health to a dentist. However, the number of utilization of dental service which is indicated by pregnant women’s dental visit data in Indonesia is still very low.This study aimed to determine factors associated with dental care visit among pregnant women.Subjects and Method: This was a cross-sectional study conducted at Klapanunggal health center, Bogor, Indonesia. A sample of 60 pregnant women was selected by consecutive sampling. The dependent variable was dental care utilization. The independent variables were oral health problem and knowledge. The data were collected by questionnaires and analyzed by a multiple logistic regression.Results: Most of pregnant women claimed that their oral health was good (35%) or average (35%). On the contrary, most of them admitted of having had at least one oral health problem (55%), including bleeding gum (35%), dental cavity (33.3%), and painfull teeth (10%). However, only 23.3% of pregnant women visited dentist during the current pregnancy. Factors associated with dental visit were existence of oral health problem (OR=6.41; p=0.019) and oral health knowledge during pregnancy (OR= 4.03; p=0.050) after controlling education, employment, income, and health insurance.Conclussion: utilization of oral health care service among pregnant women was low. Pregnant women who reported dental visit were more likely to be those who had oral health problem and who had good oral health knowledge during pregnancy.Keywords: oral health, pregnancy, antenatal care, dental visitCorrespondence: Itsna Widita, Masters Program in Quality of Health Services, Faculty of Public Health, Universitas Indonesia. Email: itsnawidita@gmail.comJournal of Health Promotion and Behavior (2019), 4(2): 145-152https://doi.org/10.26911/thejhpb.2019.04.02.07